Inhibition of IGF-I-related intracellular signaling pathways by proinflammatory cytokines in growth plate chondrocytes - Choukair, Daniela; Hügel, Ulrike; Sander, Anja; Uhlmann, Lorenz; Tönshoff, Burkhard (Pediatric research, 2014)
Children with chronic inflammatory diseases suffer from severe growth failure associated with resistance toward the anabolic action of insulin-like growth factor I (IGF-I). We hypothesized that proinflammatory cytokines interfere with IGF-I signaling.
Avance online publication 16 July 2014
Gesehen am 18.09.2020